Awakening the quieter virtues : discernment, innocence, authenticity, modesty, reverence, contentment, generosity - Spencer, Gregory H. (Gregory Horton), 1953- (Downers Grove, Ill. : IVP Books, 2010)
"Big, colorful virtues like courage and decisiveness in crisis easily get our attention. But sometimes it's those everyday values that shape us much more profoundly. Lost in our noisy, flashy, gaudy world are the quiet virtues that work behind the scenes--molding our character, guiding our actions, enriching our lives. Greg Spencer unfolds the beauty and nature of each, showing us how to take notice of discernment, innocence, generosity, authenticity and more. These qualities play a major, though often hidden, role in who we become and what we do. In each chapter you'll find practical exercises and companion spiritual disciplines to strengthen these virtues. Questions for personal reflection or group discussion offer further guidance to awakening the quieter virtues in you"--Cover, p. 4.
The Grinch was right -- Discernment : choosing life or cheering death: the discipline of attentiveness -- Innocence : lost and found : the discipline of advocacy -- Authenticity : our genuine longing : the discipline of real presence -- Modesty : it's not a modest virtue : the discipline of timely remembrance -- Reverence : the church without shoes : the discipline of astonishment -- Contentment : don't care how, I want it now! : the discipline of ars morendi -- Generosity : fingers, fists, and an open hand : the discipline of compassionate imagination -- Shouting softly.
Includes bibliographical references.
Keywords: Virtues; Christian life